2021
DOI: 10.3389/fphar.2021.771793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Puerarin on the Prevention and Treatment of Cardiovascular Diseases

Abstract: Puerarin, an isoflavone glycoside derived from Pueraria lobata (Willd.) Ohwi, has been identified as a pharmacologically active component with diverse benefits. A large number of experimental and clinical studies have demonstrated that puerarin is widely used in the treatment of a variety of diseases. Among them, cardiovascular diseases (CVDs) are the leading cause of death in the world, and therefore remain one of the most prominent global public health concerns. In this review, we systematically analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 158 publications
0
25
0
Order By: Relevance
“…Many experimental studies have indicated that puerarin can cause a reduction of AGTR1 expression in hypertension animal models. Puerarin can also boost cardiovascular function through increasing the eNOS expression and serum NO content via the PI3K/Akt pathway [ 20 ]. Vascular endothelial dysfunction can lead to various cardiovascular diseases, including hypertension, atherosclerosis, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental studies have indicated that puerarin can cause a reduction of AGTR1 expression in hypertension animal models. Puerarin can also boost cardiovascular function through increasing the eNOS expression and serum NO content via the PI3K/Akt pathway [ 20 ]. Vascular endothelial dysfunction can lead to various cardiovascular diseases, including hypertension, atherosclerosis, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that isorhynchophylline and rhynchophylline in Uncaria rhynchophylla can reflexively and directly inhibit the vasomotor center, dilating peripheral blood vessels as exertion antihypertensive effects by inhibiting the influx of extracellular Ca 2+ [16,17]. Studies have also revealed that both Salvia miltiorrhiza and Pueraria lobata have a wide variety of pharmacological effects on the cardiovascular system, including anti-inflam-matory, endothelial cell function protection, antioxidant, vasodilation, and myocardial protection [18][19][20][21]. Prunella vulgaris, Achyranthes bidentata, and Eucommia ulmoides also have therapeutic benefits for cardiovascular diseases such as hypertension [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin is an active ingredient extracted from Pueraria root that has been proven to have therapeutic effects on various cardiovascular diseases (Zhou et al, 2021). Studies have demonstrated that puerarin can prevent cardiac fibrosis by downregulating Keap1 and promoting NRF2 expression and nuclear translocation in mouse models of myocardial fibrosis (Cai et al, 2018).…”
Section: Drugs Related To Myocardial Fibrosismentioning
confidence: 99%
“…Therefore, autophagy is a key target for the treatment and prevention of heart disease. Resveratrol can upregulate autophagy, reduce collagen deposition, protect myocardium and reduce or reverse cardiac remodeling by activating AMPK/SIRT1 pathway ( Pulakat and Chen, 2020 ; Zhou et al, 2021 ). When cells (including pulmonary arterial smooth muscle) are activated by extracellular mitogenic factors such as PDGF, epidermal growth factor (EGF), fibroblast growth factor (FGF), insulin-like growth factor (IGF) and ET-1, AKT/mTOR signaling pathway plays an important role in regulating cell proliferation, migration, apoptosis and protein synthesis, most of which are related to subsequent mTOR activation.…”
Section: Possible Relevant Mechanismsmentioning
confidence: 99%